Lower body peak force but not power is an important discriminator of elite senior rugby league players - Wade, J.; Fuller, J.; Devlin, P.; Doyle, T. L. A. (Kinesiology, 2020)
This investigation determined differences in lower body strength and power between elite junior (17-20 years) and elite senior (open-aged) rugby league athletes. Twenty junior and 25 senior athletes performed an isometric mid-thigh pull, countermovement jump, repeated jump, and broad jump tests during a National Rugby League pre-season. The effects of age (junior vs. senior) and position (adjustables vs. hit-up forwards vs. outside backs) on test results were investigated using a two-way analysis of variance. Cohen`s d effect sizes (ES) and 95% confidence intervals were calculated for pairwise comparisons. Isometric mid-thigh pull absolute peak force was greater for senior players compared to junior players (ES=0.88, p<.05). Countermovement jump absolute peak power was greater for outside backs (ES=1.12) and hit-up forwards (ES=1.23) compared to adjustables (p<.05), greater for senior outside backs compared to junior outside backs (ES=1.53, p<.05), and greater for junior hit-up forwards compared to senior hit-up forwards (ES=1.00, p<.05). This research demonstrated the differences in strength and power of rugby league athletes between playing age and position. Improving lower body strength should be prioritised for athletic development of junior rugby league athletes, with consideration given to requirements across different playing positions.